Assessment of dermal exposure to organic solvents and polycyclic aromatic hydrocarbons (PAHs) among motor vehicle repair (MVR) workers: DREAM approach - Noor Fazira; Baharuddin, Mohd Rafee; Abd Rahman, Anita; Yaakub, Norwahida (Malaysian Public Health Physicians' Association, 2024)
Dermal exposure to used engine oil (UEO) and organic solvents during automobile repair, servicing, and painting is common among MVR workers. Limited studies were found on dermal assessment in Malaysia. This study focused on determining the total actual dermal exposure (ADE). A cross-sectional study was conducted on 247 MVR workers, consisting of mechanics and spray painters employed in micro and small automotive workshops located in Selangor, Malaysia. The groups completed a questionnaire to obtain socio-demographic, occupational, and health symptoms information and were observed during four specific tasks: spray painting, spray gun cleaning, flushing of UEO, and cleaning engine parts. Relevant data was gathered and an ADE assessment was conducted using the DREAM method. Overall, dermal exposure for the spray painters was found to be higher (76.01 ± 30.97 DREAM Units, DU) than for the mechanics (65.13 ± 5.02 DU). Spray painting tasks had moderate to high rankings with a mean ADE of 105.70 ± 11.92 DU (p < 0.01), the predominant routes being deposition followed by emission. Cleaning and oil flushing tasks resulted in moderate exposure. The ADE for UEO flushing was 61.93 ± 2.05 DU, for engine cleaning 69.11 ± 5.14 DU and for cleaning of spray guns 46.32 ± 1.93 DU (p < 0.01). The emission pathway was identified as the principal route of exposure and hands were the most exposed area. Clothing protection factors of hands and body parts scored minimally. The MVR workers faced significant susceptibility to occupational diseases as a result of exposure. Therefore, it is crucial to prioritise skin protection and to provide adequate training.